2006
DOI: 10.1093/hmg/ddl394
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral abnormalities precede neuropathological markers in rats transgenic for Huntington's disease

Abstract: Huntington's disease (HD) is caused by an expanded CAG repeat leading to the synthesis of an aberrant protein and to the formation of polyglutamine (polyQ)-containing inclusions and aggregates. Limited information is available concerning the association of neuropathological markers with the development of behavioral markers in HD. Using a previously generated transgenic rat model of HD (tgHD rat), we performed association studies on the time-course of behavioral symptoms (motor function, learning, anxiety) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
111
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 47 publications
24
111
1
Order By: Relevance
“…Histopathological hallmark is the accumulation of htt aggregates in affected brains (Difiglia et al, 1997;Gutekunst et al, 1999;Maat-Schiemann, 2007) which can be identified by immunohistochemistry with the so-called EM48, a widely used antibody which specifically detects N-terminal htt aggregates in brains of HD individuals and HD animal models Hodgson et al, 1999;Nguyen et al, 2006;von Hörsten et al, 2003). The role of htt aggregates and neurodegeneration is still controversial.…”
Section: Huntington Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological hallmark is the accumulation of htt aggregates in affected brains (Difiglia et al, 1997;Gutekunst et al, 1999;Maat-Schiemann, 2007) which can be identified by immunohistochemistry with the so-called EM48, a widely used antibody which specifically detects N-terminal htt aggregates in brains of HD individuals and HD animal models Hodgson et al, 1999;Nguyen et al, 2006;von Hörsten et al, 2003). The role of htt aggregates and neurodegeneration is still controversial.…”
Section: Huntington Diseasementioning
confidence: 99%
“…Among all Huntington animal models generated until now (and including the two extensively studied R6/2 and YAC128 mice), the tgHD rat is unique as it shows most prominent accumulation of htt aggregates in structures of the VSP and the EA (Niescery et al, 2009;Petrasch-Parwez et al, 2007). Moreover, it presents very early and ongoing emotional changes, which partly may be associated with dysfunctions of the VSP and EA (Bode et al, 2008;Faure et al, 2011;Nguyen et al, 2006). The distribution of htt accumulates in the medioventral striatum including the olfactory tubercle ( Fig.…”
Section: The Transgenic Huntington Rat -A `Limbic Huntington Model´mentioning
confidence: 99%
“…An Ugo Basile accelerating rotarod (model 7750) for rats, supplied by Technical & Scientific Equipment GmbH (TSE GmbH, Bad Homburg, Germany) was used, and training as well as experiments were conducted as described previously (12). For monitoring home cage activity, an infrared sensor controlled recording system (model No.…”
Section: Determination Of Motor Functions (Accelerod Test) and Circadmentioning
confidence: 99%
“…Shuttle box conditioning was used as a test of associative learning and was conducted using a TSE shuttle box system (TSE Systems GmbH) following the protocol as described previously (12). PPI of a startle response is the phenomenon in which a weak prepulse suppresses the response to a startling stimulus.…”
Section: Two-way Active Avoidance Shuttle Box Learning and Test Of Prmentioning
confidence: 99%
See 1 more Smart Citation